Mental fatigue measured in real-world sport settings: A case study of world class beach volleyball players - da Costa, Y. P.; Fortes, L.; Santos, R.; Souza, E.; Hayes, L.; Soares-Silva, E.; Batista, G. R. (Journal of Physical Education and Sport, 2023)
This study aimed to investigate mental fatigue experienced by beach volleyball players during Brazilian Beach Volleyball Tournament. The perception of mental fatigue pre-to-post-match, and perception after a win or loss were compared. A secondary aim was to associate mental fatigue with technical-tactical efforts. Seven senior world class beach volleyball players participated. A total of 30 official matches was analyzed, and seven senior world class beach volleyball players participated. The data were collected throughout national Tournaments Elite Top 8, and a digital platform accessed by the athletes' smartphones was used. A digital visual analogic scale (VAS) anchored 0 - 100 was used to measure subjective mental fatigue and technical-tactical effort. A one way repeated measures ANOVA revealed a difference pre-to-post-match for perceived mental fatigue [F(1.82 29.26)= 6.152; p= 0.007; np2 = 0.278, large effect; power= 0.833] and cubic trend [F(1.00 16.00) = 19.677; p < 0.001; mp2 = 0.552, large effect; power= 0.986]. Moreover, subjective mental fatigue was higher after losing an official match (Win: 54.14 ±23.24 Vs. Loss: 69.66 ±27.24; p = 0.064; ES = 0.639, moderate effect), and linear regression identified a relationship between subjective mental fatigue and technical-tactical effort (R2 = 0.47; p < 0.001). In conclusion, increased mental fatigue was observed in world class beach volleyball players after official matches, and losing a match seemed to augment this response. Moreover, 47% of variation in subjective mental fatigue after an official match was explained by technical-tactical effort. Therefore, athletes should avoid cognitive activities immediately prior to official matches. It is possible that resistance to mental fatigue is a contributor to success in an official beach volleyball match, but this requires further investigation.